STRUKTUR SLOT DALAM IKLAN MEDIA LUAR RUANG [Structure of Slot in Outdoor Media Advertisement] - Wening Handri Purnami (TOTOBUANG, 2017)
Advertisement is an effective tool in messaging. The content of advertisement can be social, political, economic, and so forth for the readers of the lower classes to the upper class. The intended information can be a promotion of a product or an appeal. This study examined the slot structure of outdoor media advertisement. The theory used was structural. This research used qualitative descriptive method and observation technique. Discussion of discourse structures was found in outdoor media advertisement. There are thirteen discourse structures containing name slots, specification slots, attribution slots, and address slots. The thirteen patterns of discourse structure were (1) the address-specification-attribution-address component, (2) the address-specification component, (3) the address-name-attribution component, (4) the address-attribution specification, 5) Component name-specification, (6) component name-specification, (7) address-address component, (8) component-attribution specifications, (9) address-specific components, (10) 11) component names, (12) component specifications, and (13) component attributes.Iklan merupakan sebuah sarana yang dipandang efektif dalam penyampaian pesan. Isi iklan dapat berupa informasi social, politik, ekonomi, dan lain sebagainya bagi pembaca kalangan bawah hingga kalangan atas. Informasi yang dimaksudkan dapat berupa promosi mengenai suatu produk atau imbauan. Penelitian ini mengkaji struktur slot pada iklan media luar ruang. Teori yang digunakan adalah struktural. Penelitian ini menggunakan metode deskriptif kualitatif dan teknik observasi. Hasil pembahasan terkait struktur wacana ditemukan dalam iklan media luar ruang. Terdapat tiga belas struktur wacana yang berisi slot nama, slot spesifikasi, slot atribusi, dan slot alamat. Ketiga belas pola struktur wacana tersebut adalah (1) berkomponen nama-spesifikasi-atribusi-alamat, (2) berkomponen nama-spesifikasi-alamat, (3) berkomponen nama-atribusi-alamat, (4) berkomponen spesifikasi-atribusi-alamat, (5) berkomponen spesifikasi-nama-atribusi, (6) berkomponen nama-spesifikasi, (7) berkomponen nama-alamat, (8) berkomponen spesifikasi-atribusi, (9) berkomponen spesifikasi-alamat, (10) berkomponen atribusi-nama, (11) berkomponen nama, (12) berkomponen spesifikasi, dan (13) berkomponen atribusi.